"Communists They May Have Been": Australian Maritime Unionists and the National Shipping Line, c. 1950–90. (May 2019) - Ostapenko, Dmytro
Abstract : Australian maritime unions of the Cold War period are renowned for their militancy and rhetorical commitment to communist ideas. In contrast, concentrating on the policies and actions of the Seamen's Union of Australia (SUA) and the Waterside Workers' Federation (WWF) towards the Australian National Line (ANL), this article reveals their political and industrial pragmatism in advancing a national shipping agenda. It demonstrates that union support of the Line took two main forms. First, maritime unionists sought to protect the state-owned shipping company from unfair international competition by launching protest actions against substandard foreign carriers. Second, they willingly cooperated with Australian shipping industry stakeholders to boost seagoing labour productivity and thus the global competitiveness of the ANL. The article argues that it was the increasing integration of the Australian maritime enterprise into the highly competitive global shipping market that prompted the SUA and the WWF to take an active role in defending national shipping interests.